Adab Sebagai Politik Hukum Islam - Yogi Prasetyo (Universitas Darussalam Gontor, 2017)
This paper aims to know the concept of adab as the politics of Islamic law. Only Islam has the adab to organize people in all spheres of life while still being able to keep up with the times. Islam as a civilized religion wants the good of the world and here after by making human beings as khamil who believe and piety to Allah SWT is evidenced by obedience to His laws as dijelskan in al-Qur’an and Hadith. Adab is a basic principle typical of Islam which contains the values and rules of law that govern human life. Adab contains an inner philosophy of life that explains the lives of the past, present and future. The dimensions of space and time covered in adab can always follow global developments, so that there is an eternal politics of Islamic law as a way for the Islamic law that governs the good of human beings to be the main grip in living life. It is important that the role of adab in the development of the ummah, because it contains about the laws of Allah SWT to regulate acceptable human life and become the main need to practice it, because the goodness that is in it is desired by the whole people. The value contained in it is able to reduce the egoism and fanatic sentiments that are often spread by interested parties. As the politics of Islamic law, adab contains the wisdom of life, contained in it can provide widespread benefit to all mankind.